Manajemen Risiko Pengangkutan Bahan Bakar Nabati Biodiesel untuk Kebutuhan dalam Negeri - Abidin, Zaenal; Suseno, Effan Dwi; Pahala, Yosi; Maemunah, Siti; Sijabat, Eduard Alfian Syamsya (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2024)
The main problem of the study is related to transportation of goods that cannot be separated from the risks of the goods and the field condition. Based on the previous observation, there were five risk’s categories of biodiesel fuel transportation; force majeure risk, risk of equipment or transportation mode of distribution pipe, risk of equipment or tanker transportation mode, workforce risk, and system and procedural risk. The purpose of the research is to analyze the risk identification, the risk assessment and the risk control of biodiesel fuel transportation from PT XYZ in South Kalimantan to Pertamina Wayame Ambon Maluku. The research method used the risk assessment with Likert scale. The research found that there are three types of risks with the same average score (risk of equipment or transportation mode of distribution pipe, risk of equipment or tanker transportation mode, and workforce risk) and four types of risks that have cost greatest impact of the medium category (force majeure risk, risk of equipment or transportation mode of distribution pipe, risk of equipment or tanker transportation mode, workforce risk).